2015
DOI: 10.1136/thoraxjnl-2014-206416
|View full text |Cite
|
Sign up to set email alerts
|

Identifying areas and risk groups with localisedMycobacterium tuberculosistransmission in northern England from 2010 to 2012: spatiotemporal analysis incorporating highly discriminatory genotyping data

Abstract: Incorporating highly discriminatory genotyping data into spatiotemporal analysis of TB incidence is feasible as part of routine surveillance and can provide valuable information on groups at greater risk and areas with localised transmission of TB, which could be used to inform control measures, such as intensified contact tracing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Previous studies have found sociodemographic factors to be predictors of recent TB transmission, such as younger age, minority race/ethnicity status, male sex, homelessness, incarceration, and drug use. 17,18 In our study, domestic overcrowding and social class were associated with genetic clustering, indicating that poverty and socioeconomic status, which are known factors associated with the risk of developing TB, 19 are also linked to recent transmission of the disease in the indigenous population.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies have found sociodemographic factors to be predictors of recent TB transmission, such as younger age, minority race/ethnicity status, male sex, homelessness, incarceration, and drug use. 17,18 In our study, domestic overcrowding and social class were associated with genetic clustering, indicating that poverty and socioeconomic status, which are known factors associated with the risk of developing TB, 19 are also linked to recent transmission of the disease in the indigenous population.…”
Section: Discussionmentioning
confidence: 52%
“…These approaches were combined to quantify the role of recent transmission and determine geographical locations of such transmission in 25 studies. This was done either by determining the spatial distribution of genotypic clusters [ 25 , 28 , 59 69 ] or by assessing the genotypic similarity of cases contained within geospatial clusters [ 2 , 57 , 65 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…These analyses have been used to identify areas of likely TB transmission. [6][7][8][9][10][11][12][13][14] Visualisation of spatial data on maps also provides a powerful means of communicating information about the disease to policy makers and the public.…”
Section: Introductionmentioning
confidence: 99%